- Does electricity consumption influence economic growth in Indonesia? - Vita Kartika Sari Sari (Economic Research Center, the Indonesian Institute of Sciences (P2E-LIPI), 2022)
The purpose of this study was to analyze the influence of electricity consumption, investment, and school enrollment on economic growth of Indonesia from 1984-2018. Electricity is used by society in every activity including production and consumption. This study used ARDL-ECM method. Based on the estimation results, all variables were stationary at the first difference. Based on the empirical findings, the appropriate ARDL model was ARDL (1, 2, 1, 1). In the long run, investment had a positive influence on economic growth and school enrollment had a negative influence on economic growth. Meanwhile, in the long run, electricity consumption is insignificant to the economic performance of Indonesia during the study period. However, in the short run, there was only investment had a significant and positive impact on economic growth in Indonesia. School enrollment and electricity consumption had no significant influence on economic growth. Speed of adjustment (ECT (-1)) had a significant influence on GDP. With the Qusum and QusumQ tests, the model showed feasible stability. Therefore, more vigorous electricity policies should be implemented for supporting economic growth.